Corals of Pulau Perak: after 46 years of scientific solitude - Yang Amri, Affendi; Huzaimi Tajuddin, Badrul; Ai Lin, Yong,; Abdul Adzis, Kee Alfian (Malaysian Journal of Science, 2008)
Underwater surveys were done at Pulau Perak in 2004 and 2006 to investigate whether corals were present after the last scientific expedition in 1958. Using a modified Reef Check method at two study stations at 5 m and 15 m depths, it was documented that corals were not only present but had a high cover of up to 58%. Abundant fish life and high numbers of the banded coral shrimp were observed. A very distinct Crown-of-Thorns Sea Star population unlike the ones found in other Malaysian waters was also documented. The island and its surrounding water should be declared a marine park as it harbours a rich diversity of pristine corals and other marine life.